Acervo do Departamento de Arquivo Geral: preservação da memória da UFSM - Flores, Débora (2011)
This research addresses the preservation of UFSM s documental heritage, which is stored on the collection of the General Archive Department (Departamento de Arquivo Geral (DAG)), and aims at contributing for the permanent safeguard of these documents by means of the adoption of a Manual of Preservation of Documents. We also consider the risks the professionals of the archive face by having direct contact with the documents, because exposure to some types of fungi can trigger damages to health, seriously affecting their life quality. It is an applied research, of qualitative approach, which aims at developing knowledge that enables comprehension and transformation of reality regarding the topic. The work has been structured into four phases: the first phase consists of data collection by means of a diagnosis of the collection situation. The diagnosis was carried out based on direct observation, and, with the obtained data, it was possible to detect the needs for a better preservation of the documental collection under custody of DAG. At this phase, we could identify the need to implement the Manual, and the need of applying the measurements which would prevent the deterioration of UFSM s documental heritage. On the second phase, the monitoring of temperature and humidity was carried out, resulting in graphs which indicate great climate variation in the documents storing rooms. Thus, actions should be applied for the use of equipments which ensure effective climate control, preventing damage to the documents. For the verification of the presence of fungi in the collection, different species were found, both in the documents which form the collection, as in the documents recoiled to DAG. Implementation of hygiene procedures is vital in the documentation. In face of the biological risks, we have tried to analyze the damages to the health of the professionals which work at the archive. This resulted in identification of allergic reactions, which, although not grave, compromise the life quality of the professionals in the long term. Thus, the use of personal protective equipment is indispensable for handling the documents of the collection. The research showed that much has already been done by DAG to protect the collection. However, only through study and concrete knowledge of the main measures that must be adopted it was possible to organize such measures, which, systematically gathered through the Manual of Preservation of Documents, will proportionate a better safeguarding of the Documental Heritage of UFSM.